Delineation of Wellhead Protection Areas in Crete, Greece Using an Analytic Element Model. (2016) - Staboultzidis, Alexandros; Dokou, Zoi; Karatzas, George P.
Abstract: Groundwater is one of the main sources of drinking water in many regions and therefore investing in its protection is of paramount importance. A very important step in ensuring water of good quality is the delineation of well head protection areas (WHPAs), which is the focus of this research. The area of interest is the basin of the Keritis River, located near the city of Chania, Crete, Greece. The main contamination threats in the area are: i) olive oil industries ii) cemeteries and iii) urban waste from the towns located near or within the basin. The delineation of WHPAs in this work is performed using a more accurate method than a simple fixed radius around the well, which is currently common practice in Greece. A decision support modeling tool called Wellhead Analytical Element Model (WhAEM) was used for this purpose. WhAEM is a groundwater flow model designed to facilitate the delineation of capture zones and mapping well head protection, using the analytic element method. The unique hydrogeology of the modeled area (location of local heterogeneities, discontinuities, rivers, recharge, no-flow boundaries) is taken into account in order to prevent potentially harmful contaminants reaching the water supply. This process can be used as a management tool by water resources managers, stakeholders and public authorities in order to impose rational measures and potential restrictions in urban, agricultural and industrial activities developed in the area.